Blood component separation of pathogen‐reduced whole blood by the PRP method produces acceptable red cells but platelet yields and function are diminished. Issue Volume 60:Issue S3(2020) (1st June 2020) - Herzig, Maryanne C.; Fedyk, Chriselda G.; Montgomery, Robbie K.; Schaffer, Beverly S.; Bynum, James A; Pidcoke, Heather F.; Cap, Andrew P.
Abstract : BACKGROUND: This study evaluated blood components processed by the platelet rich plasma (PRP) method from fresh whole blood (FWB) treated with a pathogen reduction technology (PRT). The effects of storage temperature on PRT treated platelet concentrates (PCs) were also examined. STUDY DESIGN AND METHODS: PRT was performed using riboflavin and ultraviolet light on FWB in citrate phosphate dextrose anticoagulant. Following PRT, red blood cells (RBCs), PCs, and plasma for fresh frozen plasma (FFP), were isolated by sequential centrifugation. RBCs were stored at 4°C, FFP at −80°C, and PC at 22°C or at 4°C. Components were assayed throughout their storage times for blood gases, chemistry and CBC, hemostatic function as well as platelet (PLT) and RBC integrity. RESULTS: Component processing following PRT resulted in a significant drop in platelet recovery. Most PRT‐PC bags fell below AABB guidelines for platelet count. PRT‐PC also showed a decrease in clot strength and decreased aggregometry response. Platelet caspases were activated by PRT. Storage at 4°C improved platelet function. In PRT‐FFP, prothrombin time and partial thromboplastin time (PT and aPTT) were prolonged; factors V, VII, VIII, and XI, protein C, and fibrinogen were significantly decreased. Free hemoglobin was elevated two‐fold in PRT‐RBC. CONCLUSION: Blood components isolated by the PRP method from PRT‐treated WB result in a high percentage of PC that fail to meet AABB guidelines. FFP also shows diminished coagulation capacity. However, PRT‐RBC are comparable to control‐RBC. PRT‐WB retains acceptable hemostatic function but alternatives to the PRP method of component separation may be more suitable.